Questioning the effectiveness of the Natura 2000 Special Areas of Conservation strategy: the case of Crete - Panayiotis G. Dimitrakopoulos; Dimitris Memtsas; Andreas Y. Troumbis (Global Ecology and Biogeography, 2004)
Aim This study examines the effectiveness of the selected ‘network’ of Natura 2000 Special Areas of Conservation (SACs) at a regional scale in Greece, in terms of its representativeness of plant biodiversity. Location The island of Crete is used as a case study because it is considered to be one of the 10 hotspots for biodiversity in the Mediterranean Basin. Methods Hotspot analysis and complementarity algorithms are used to define priority areas for conservation and calculate their spatial overlap with the Natura 2000 SACs in Crete. Results The various categories of hotspots contain subsamples of plant categories, used for their definition. Spatial overlap among different categories of hotspots, areas of complementary diversity and Natura 2000 SCAs is low. Main conclusions The results show that the Natura 2000 SACs ‘network’ in Crete seems insufficient to ensure satisfactory representation of the regional plant biodiversity elements.